Nilai-Nilai Pendidikan Islam Berbasis Kearifan Lokal: Kain Sasirangan Khas Banjar - Syahida Ajrina; Zulfa Jamalie; Fasih Wibowo (Jurnal Kajian Islam dan Sosial Keagamaan, 2026)
Sasirangan cloth is a traditional cloth of the Banjar people that represents a form of local wisdom in South Kalimantan. This study aims to examine and describe the values of Islamic education embedded in sasirangan cloth as a distinctive form of local wisdom of South Kalimantan, so that it may serve as a medium and source of Islamic education relevant to the life of the Banjar people. This research employs a library research design using a qualitative approach to review, examine, and analyze various literature sources, including books, journals, and research articles related to Islamic educational values based on local wisdom within the concept of sasirangan cloth of South Kalimantan. The findings indicate that sasirangan cloth can function as a medium and source of learning through the presence of Islamic educational values contained in its various motifs, such as religious values represented by the star motif, values of strength represented by the kangkung kaumbakan and ombak sinapur karang motifs, the value of independence represented by the kulat karikit motif, the value of harmony represented by the pucuk rabung motif, and the value of nationalism represented by the laju bakayuh motif.